9x+8=89x

Simple and best practice solution for 9x+8=89x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+8=89x equation:


Simplifying
9x + 8 = 89x

Reorder the terms:
8 + 9x = 89x

Solving
8 + 9x = 89x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-89x' to each side of the equation.
8 + 9x + -89x = 89x + -89x

Combine like terms: 9x + -89x = -80x
8 + -80x = 89x + -89x

Combine like terms: 89x + -89x = 0
8 + -80x = 0

Add '-8' to each side of the equation.
8 + -8 + -80x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -80x = 0 + -8
-80x = 0 + -8

Combine like terms: 0 + -8 = -8
-80x = -8

Divide each side by '-80'.
x = 0.1

Simplifying
x = 0.1

See similar equations:

| 56=8z | | logk=20 | | 35=7s | | 0.5x=12x | | 24=3v | | 2+8m=18m | | 18=9c | | 8n+50=109 | | 24=2B+g | | (0,3/0,01)*2*((0,2*1,9*10^3)/(N*0,3*0,9))^(1/3)*(12/6)^(0,14) | | 4a^2-20a-24=0 | | 3x+5y+2z=2 | | -p^2+p+20=0 | | 4e=24 | | -3p-(-3)/-6=-12 | | 36=9m | | 7x-11/5x-2=2x-9/5x-2 | | 2x=9-5x+32 | | t+8=4t+5 | | 8z-6=7z | | ((x^2-ax-8)/(x-a))=0 | | 8(x-8)=4(x+4) | | (3x-4)(2x+5)=20 | | N^(2/3)=12,5 | | 2x+46=320 | | 5x+6+4x=-3(x-8)+7x | | (3.0075-6.0215)+t=2.105 | | x^3-x^2+2x-1=0 | | -5x+3=-6-2x | | 11(v+1)-3v=4(2v+4)-25 | | 3x-7x=-8 | | 2.7(x-8)=-2.7(x+15) |

Equations solver categories